The good and bad of ambivalence Desiring ambivalence under outcome uncertainty. [article]. - Reich, Taly.
Decades of past research point to the downside of evaluative inconsistency (i.e., ambivalence), suggesting that it is an unpleasant state that can result in negative affect. Consequently, people are often motivated to resolve their ambivalence in various ways. We propose that people sometimes desire to be ambivalent as a means of strategic self-protection. Across employment, educational and consumer choice settings, we demonstrate that when people are uncertain they can obtain a desired target, they will cultivate ambivalence in order to protect their feelings in the event that they fail to get what they want. Specifically, we show that people consciously desire to cultivate ambivalence as a way to emotionally hedge and that they seek out and process information in ways to deliberately cultivate ambivalence. We find that people are most likely to generate ambivalence when they are most uncertain that they can obtain their desired target. Depending on the outcome, this cultivated ambivalence can either be useful (when the desired target is not obtained) or backfire (when the desired target is obtained). -- (from the authors)
Keywords: Wheeler, Christian; Ambivalence; Self-protection strategy; Self-evaluation.; Attitudes; Self-affirmation.